Chlorophyll Fluorescence and Reflectance-Based Non-Invasive Quantification of Blast, Bacterial Blight and Drought Stresses in Rice - Šebela, David; Quiñones, Cherryl; Cruz, Casiana V; Ona, Isabelita; Olejnícková, Julie; Jagadish, Krishna S V (Plant & cell physiology, 2018)
Response of rice (Oryza sativa) exposed to both biotic and abiotic stresses can be quantified by employing fast and accurate optical methods. In this study, the overall stress responses of (i) 12 near-isogenic lines (NILs) in the genetic background of the rice blast-susceptible cultivar Lijiangxintuanheigu (LTH) and (ii) four NILs in the genetic background of the bacterial blight-susceptible cultivar IR24, were inspected by means of Chl fluorescence (Chl-F) imaging. The distribution of the maximum and effective quantum yield of PSII (Fv/FM and QY) and steady-state Chl-F (Ft) were found to be effective in differentiating symptomatic leaf tissue for both rice blast and bacterial blight, which correlated well with 30 cycles of rice blast and six cycles of bacterial blight previously screened using classical (manual) approaches. Subsequently, identified Chl-F parameters allowing detection under ambient light (QY and Ft) were tested across both biotic and abiotic (drought) stress experiments, for rice cultivars contrasting for drought stress response (N22, IR64 and NSIC Rc 222). Their applicability has been proven for both rice blast and bacterial blight; however, QY failed to detect the effect of drought. In addition to Chl-F, the usefulness of 11 selected vegetation indices (Vis) was tested on these three cultivars exposed to particular stresses: (i) rice blast was detectable by Vis calculated from the visible spectrum; (ii) bacterial blight by near-infrared-related Vis; and (iii) drought by Vis calculated from the visible spectrum. The key Chl-F parameters and/or Vis have been summarized and discussed.
Keywords: Chlorophyll; Plant Leaves; Photosystem II Protein Complex; fyziologický stres; Fluorometry; Magnaporthe; Xanthomonas; Host-Pathogen Interactions; rýže (rod); Reflectance; Plant Diseases; Spectrophotometry; interakce hostitele a patogenu; Drought stress; Chlorophyll fluorescence; chlorofyl; regulace genové exprese u rostlin; listy rostlin; Gene Expression Regulation, Plant; Fluorescence; Stress, Physiological; fotosystém II (proteinový komplex); Bacterial blight; Rice bast; Oryza; fluorometrie; nemoci rostlin; spektrofotometrie; fluorescence; období sucha; Droughts